PENGARUH RASIO PROFITABILITAS (RETURN ON ASSET DAN RETURN ON EQUITY) HARGA SAHAM PERBANKAN YANG TERDAFTAR PADA LQ45 (Magister Manajemen Universitas Wisnuwardhana, 2022)
This study assesses financial performance in the short term by using liquidity ratios and profitability ratios. The liquidity ratio describes the company's ability to pay its financial obligations that must be met immediately, which consists of the Current Ratio and Quick Ratio. The profitability ratio is used to measure the company's ability to generate profits in the form of ROA and ROE. The company will try to maximize the value of its shares which is indicated by its share price. This study aims to analyze how much influence the profitability ratios, namely ROA and ROE, on the stock prices of the banking sector included in the LQ45 list. This type of research is a review article by taking research that has been done previously.